2015
DOI: 10.5853/jos.01389
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Painting Style by Poststroke Mania

Abstract: Letter to the EditorDear Sir:Post stroke neuropsychiatric syndrome is common.1 Many patients after stroke experience depression, cognitive impairment, personality change, psychosis, apathy, and anxiety. Mania can also be a consequence of stroke but is not common.2 "Mania" is described as a distinct period of abnormally and persistently elevated, expansive, or irritable mood, lasting at least 1 week in the Diagnostic and Statistical Manual of Mental Disorder-V.3 Mania seems to be observed more frequently with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
2
4
0
1
Order By: Relevance
“…Findings regarding the classification of constructive errors in paining showed that omission errors were most common in patients with stroke-inducted neglect. Omission error outcome was consistent with studies on professional artists (Bäzner & Hennerici, 2006;Blanke & Pasqualini, 2012;Rhee et al, 2016). Right-hemisphere stroke patients showed mostly left space omission errors and changes in painting style (J.-M. H. H.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Findings regarding the classification of constructive errors in paining showed that omission errors were most common in patients with stroke-inducted neglect. Omission error outcome was consistent with studies on professional artists (Bäzner & Hennerici, 2006;Blanke & Pasqualini, 2012;Rhee et al, 2016). Right-hemisphere stroke patients showed mostly left space omission errors and changes in painting style (J.-M. H. H.…”
Section: Discussionsupporting
confidence: 84%
“…However, there is limited research into therapy for adults with acquired art constructive errors in painting. Previous studies on the art constructive errors of painting were focused on after stroke effects in professional painters (Pachalska et al, 2008;Rhee et al, 2016). Although patients in our study were not professional painters, they presented errors in the painting like professional painters after stroke.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…По данным метаанализа [8], самыми частыми симптомами постинсультной ма-нии были повышенное настроение (91%), патологи-ческая говорливость (71%), сниженная потребность во сне (69%), ажитация (63%). Описан случай изме-нения стиля рисования у художника с симптомами мании после инсульта в системе средней мозговой артерии [31]. Метаанализ позволил выявить наибо-лее характерные особенности пациентов с постин-сультной манией.…”
unclassified